2011
DOI: 10.1007/s12550-011-0112-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in South African foods: a case study on aflatoxin M1 in milk

Abstract: The contamination of cow's milk at the farm level with aflatoxin M1 was investigated in South Africa. Samples of feeds, forage, maize and milk were taken at nine dairy farms, and at the same time samples of the processed milk (retail milk) were collected from the respective dairies to which the farms delivered their milk. The feeds were analysed for aflatoxin B1 and the milk samples for aflatoxin M1 using high performance liquid chromatography (HPLC) and fluorescence detection. All milk samples from the dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Seasonal differences in concentrations of AFM1 in milk samples have also been reported [50]. A recent study [51] has shown the maximum concentration of AFs in milk marketed from small-holder dairy farms in the monsoon season in Punjab Pakistan was 2.59 ppb, whereas the lowest concentration was observed in summer (1.93 ppb).…”
Section: Aflatoxin M1mentioning
confidence: 79%
“…Seasonal differences in concentrations of AFM1 in milk samples have also been reported [50]. A recent study [51] has shown the maximum concentration of AFs in milk marketed from small-holder dairy farms in the monsoon season in Punjab Pakistan was 2.59 ppb, whereas the lowest concentration was observed in summer (1.93 ppb).…”
Section: Aflatoxin M1mentioning
confidence: 79%
“…It may be screening, confirmatory or both. The most reported methods conventionally used for AFM1 extraction and detection are liquid-liquid extraction, silica gel, SPE cartridges (C18) cartridges [50] or immunoaffinity column (IAC), [57]. The inconvenience of this method is excessive use of chlorinated solvent in liquid-liquid extraction [21].…”
Section: Update On Aflatoxin M1 Extraction Detection and Quantificatmentioning
confidence: 99%
“…This is simple, quick, and more stable than IAC [54] will probably be used for AFM1 in the future as there have been no reports on this. Reports have shown that the detection and quantification of AFM1 can be done by separation using thin-layer chromatography (TLC) or high-performance liquid chromatography (HPLC) coupled with fluorescence detector [6,[55][56][57]. The inconvenience of the TLC method is that it is challenging in the determination of mycotoxin concentrations with exactitude.…”
Section: Update On Aflatoxin M1 Extraction Detection and Quantificatmentioning
confidence: 99%
See 2 more Smart Citations